Significant contributors to cost overruns in construction projects of Cambodia. Issue 1 (1st January 2017) - Durdyev, Serdar; Omarov, Maksat; Ismail, Syuhaida; Lim, Mengheng
Abstract: Construction industry is one of the leading sectors with its remarkable contribution to the GDP and employment generation in Cambodia. However, one of the major challenges facing the construction industry in Cambodia is poor cost performance of the construction projects. Identifying and addressing the contributors to cost overruns in the residential building projects—which attracts the highest proportion of investment—is crucial for improving the cost performance of the sector. In the absence of related research in Cambodia, this study aims to fill a significant knowledge gap by investigating the key contributors to cost overruns in residential projects which are specific to the operational context of the Cambodia's residential building sector. Feedback from a survey of the sector's contractors and project managers was analysed using an exploratory factor analysis. Results showed three principal contributors to cost overruns which were extracted from 26 variables: Project and cost management, project finance and project risks factors. In diminishing order of influence, these accounted for 53, 22 and 16%, of the variance that characterized poor cost performance output in the sector. By focusing available resources and efforts on these key factors in relation to their magnitudes of influence, contractors, project managers and clients could minimise the cost overruns and improve significantly cost performance of the sector and its contribution to the nation's economy.